Kroppen som hovedtema i Pia Tafdrups forfatterskab - Cymbrykiewicz, Joanna (Folia Scandinavica Posnaniensia, 2007)
The article presents the category of the body as a thematic motif in the poetry of one of the most notable contemporary Danish poets, Pia Tafdrup. In her poetry the human body is perceived from the specific perspective of a woman writer, whose sensuality, female sexuality and physiology constitute a source of inspiration and a starting point for spontaneous artistic creativity. In the article two subcategories are mentioned with reference to the body motif. The first one focuses on the celebration of human sensuality in all its respects, whilst the other presents the woman’s body and its physiology as an immanent part of nature and proof of the so-called “universal memory”. This creation of a specific “body philosophy”, deeply rooted in the conditions of a woman artist and highly subjective in its perception of the world becomes the culminating principle of the article.